Tense Interactions in Times of Uncertainty - Očková, Katarína (Lidé města, 2023)
This thematic issue sheds light on navigations of otherness and relations of mistrust during times of uncertainty and insecurity. These often-tense interactions take many shapes and occur within, as well as across, boundaries set in terms of ethnicity, religion, kinship, gender, political ideology, citizenship status, health risk, and contagion. As the articles in this issue demonstrate, during such uncertain times, people search for ways to negotiate tensions surrounding the relationship between sameness and otherness (Bauman 2001). This involves navigating various challenges, especially when crossing borders or symbolic boundaries, while carefully following the processes involved in creating and maintaining them. Additionally, individuals may have to face inequalities, structural violence, xenophobia, and rising extremism. Furthermore, they may need to negotiate issues of mistrust and risk in contexts of contagion, illness, and (mis)information. And, sadly, many people are forced to navigate the effects of critical events (Das 1995) on their everyday life and social relationships in contexts of conflict and crisis.